2016
DOI: 10.1139/bcb-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into RAD51 activity and regulation during homologous recombination and DNA replication

Abstract: In this review we focus on new insights that challenge our understanding of homologous recombination (HR) and Rad51 regulation. Recent advances using high resolution microscopy and single molecule techniques have broadened our knowledge of Rad51 filament formation and strand invasion at double-strand break (DSB) sites and at replication forks, which are one of most physiologically relevant forms of HR from yeast to humans. Rad51 filament formation and strand invasion is regulated by many mediator proteins such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 136 publications
(235 reference statements)
5
87
0
1
Order By: Relevance
“…S2F), while total ATM expression remained unchanged. In addition, Rad51, a single-stranded DNA-binding protein responsible for HR repair (21,22), showed modest increases in CTCF depleted cells. In contrast, the ATR kinase was only minimally affected by the knockdown (Fig.…”
Section: Ctcf Prevents Genomic Instabilitymentioning
confidence: 99%
“…S2F), while total ATM expression remained unchanged. In addition, Rad51, a single-stranded DNA-binding protein responsible for HR repair (21,22), showed modest increases in CTCF depleted cells. In contrast, the ATR kinase was only minimally affected by the knockdown (Fig.…”
Section: Ctcf Prevents Genomic Instabilitymentioning
confidence: 99%
“…How these modifications affect the dynamics of nucleoprotein filament assembly and stability remains to be determined. More importantly, the RAD51-DNA interactions are controlled by the recombination mediator BRCA2, by RAD51 paralogs and Shu complex (Zelensky et al, 2014, Prakash et al, 2015, Godin et al, 2016), by antirecombinogenic DNA helicases (Daley et al, 2014), and by the heteroduplex rejection machinery (Spies and Fishel, 2015). These modulators of RAD51 activity or their individual RAD51-interacting domains can be incorporated into the FRET-based, single-molecule experiments described here.…”
Section: Discussionmentioning
confidence: 99%
“…Rad51 overexpression leads to the accumulation of abnormal karyotypes and gene mutations, which are closely related to carcinogenesis and drug resistance [16]. Studies have shown that, such as breast cancer, pancreatic cancer and other tumors overexpressed Rad51 protein, positively correlated to tumor histological grade and stage [17,18]. In addition, domestic and foreign researchers also found that gene polymorphism of Rad51 recognized as the risk factor of CRC carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%